Efeito do tratamento da superfície dental com os lasers Nd:YAG e Er: Yag na adesão da resina composta à dentina recém clareada - Sanches, Tatiane Caldas Quirino [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
To evaluate the effect of surface treatment with Er:YAG and Nd:YAG laser on resin composite bond strength to recently bleached dentin. Material and Methods: In this study 120 bovine incisors were used and distributed into two groups: Group C: without bleaching treatment; Group B: with bleaching treatment (35% hydrogen peroxide). Each group was divided into three subgroups: Subgroup N: without laser treatment; Subgroup Nd: irradiation with Nd:YAG laser; Subgroup Er: irradiation with Er:YAG laser. Next, the adhesive system (Adper Single Bond 2) was applied and composite buildups were constructed with Z350 composite. The teeth were sectioned to obtain dentin-resin sticks (1x1mm) and analyzed by microtensile bond testing. The data were statistically analyzed by the ANOVA and Tukey tests. Results: The results showed that the bond strength values in the bleached control group (16.17 MPa) presented no significant difference in comparison with the group bleached and irradiated with Er:YAG laser (14.69 MPa). The non bleached control group (26.79 MPa) presented significant difference in bond strength when compared with the non bleached group irradiated with Er:YAG laser (22.82 MPa) and with the group treated by bleaching and irradiation with Nd:YAG laser (28,792 MPa). The group without bleaching treatment and irradiated with Nd:YAG (36.1 MPa) presented a significant increase in bond strength in comparison with the other groups. Conclusion: The use of Nd:YAG laser on bleached specimens was able of completely reversing the immediate effects of bleaching, obtaining bond strength values similar to those of the control group

O objetivo desta pesquisa foi avaliar o efeito do tratamento de superfície com os lasers Er:YAG e Nd:YAG na resistência adesiva à dentina recémclareada. Foram utilizados 120 dentes bovinos divididos em dois grupos: Grupo N: sem tratamento clareador; Grupo C: com tratamento clareador (Clareamento com peróxido de hidrogênio a 35%). Cada grupo foi dividido em três subgrupos: Subgrupo S: sem tratamento com laser; Subgrupo Nd: irradiação com Nd:YAG; Subgrupo Er: irradiação com Er:YAG. A seguir foi aplicado o sistema adesivo e posteriormente confeccionados sobre a área de adesão cubos de resina composta. Os espécimes foram submetidos ao ensaio de microtração e análise do tipo de fratura. Os dados foram analisados estatisticamente pelo teste ANOVA e Tukey. Os resultados mostraram que os valores de resistência adesiva do grupo controle clareado (16,17 Mpa) não apresentou diferença significativa em relação ao grupo clareado e irradiado com Er:YAG (14,69 Mpa) .O grupo controle não clareado (26,79 Mpa) não apresentou diferença significativa na resistência adesiva em relação ao grupo não clareado e irradiado pelo Er:YAG (22,82 Mpa) e ao grupo com tratamento clareador e irradiado com o Nd:YAG (28,792 Mpa). O grupo sem tratamento clareador e irradiado pelo Nd:YAG (36,1 Mpa) apresentou aumento significativo na resistência adesiva em relação aos outros grupos. Assim concluímos que o uso do laser Nd:YAG nos espécimes clareados foi capaz de reverter completamente os efeitos imediatos do clareamento obtendo valores de resistência adesiva similares ao grupo controle
Keywords: Dentina; Adesão; Laser; Clareamento dental